2021
DOI: 10.1002/prca.202100019
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics analysis of diabetic cardiomyopathy in aging‐accelerated mice and effects of D‐pinitol

Abstract: Purpose:The molecular mechanisms of diabetic cardiomyopathy (DCM) development and D-pinitol (DP) in its treatment remain unclear. The present study is to explore the underlying mechanism of DCM in an elderly diabetic mouse model and to seek the protective targets of DP by phosphoproteomics. Experimental design:We used streptozotocin to induce diabetes in SAMP8 and DP (150 mg/kg/day) intragastrically administrated to diabetic mice for 8 weeks. The heart tissues were harvested for label-free phosphoproteomic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This, in turn, helps alleviate DCM. 32 Our research findings suggest that the deficiency of mitophagy is reduced by DP via MFG‐E8 regulation, which contributes to alleviating symptoms of diabetic sarcopenia.…”
Section: Discussionmentioning
confidence: 67%
“…This, in turn, helps alleviate DCM. 32 Our research findings suggest that the deficiency of mitophagy is reduced by DP via MFG‐E8 regulation, which contributes to alleviating symptoms of diabetic sarcopenia.…”
Section: Discussionmentioning
confidence: 67%
“…ERS plays a crucial role in the development of myocardial apoptosis and fibrosis in DCM. Endoplasmic reticulum is a complex intracellular membrane network, which regulates protein folding and modification (Li, Yu, et al, 2022; Li, Zhang, et al, 2022). A variety of factors including hyperglycemia, AGEs accumulation, oxidative stress, and ischemia, cause the accumulation of unfolded proteins, and trigger unfolded protein response, which ultimately leads to myocardial apoptosis and hypertrophy (Fernández et al, 2015; He et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research found that D‐pinitol (methyl ether of D‐chiro‐inositol, DP) could inhibit the myocardial apoptosis and fibrosis in STZ‐induced senescence‐accelerated prone 8 (SAMP8) mice. The protective effect of DP on DCM was related to the regulation of OPTN (Li et al, 2021; Li, Yu, et al, 2022; Li, Zhang, et al, 2022). DP is found in large quantities in soybean, carob pods, and legume foods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations